Is semantic feature analysis effective when applied intensively? A randomized pilot study with non-fluent aphasic individuals - Yaşa, İbrahim Can (The European Research Journal, 2023)
Objective: In this study, it was investigated the effects of intensive aphasia treatment applied to individuals with non-fluent aphasia. Methods: Sixteen patients diagnosed with non-fluent aphasia were included in the study and were randomly divided into two groups. The therapy interventions were one day per week for the eight patients in the first group, for a total of 8 hours in 2 months (standard intervention). For the eight patients in the second group, therapy was applied for a total of 48 hours in 2 months, for one hour per day, six days a week, excluding Sundays (intensive intervention). Participants were tested using the Turkish aphasia test (ADD), Aphasia Impact Scale-21 (AIQ-21), and Boston Naming Test (BNT) before starting the treatment (pretest), after the treatment (posttest), and one month after the treatment ended (follow-up). Results: At the end of the treatments, a significant increase in ADD and BNT scores and a significant decrease in AIQ-21 scores were observed in both groups. Although there was a change in the follow-up test, the scores were still significantly different than the pretest scores. The rate of improvement in test scores of group II patients who received intensive aphasia treatment was superior to the group I patients. Conclusion: Intensive application was superior to once-weekly aphasia treatment, and post-treatment improvement continued for at least one month after the treatments.